Pengaruh Daya Tarik, Keahlian, dan Kepercayaan Selebgram Terhadap Minat Beli Konsumen Pada Produk Scarlett Whitening (Studi Kasus Pada Mahasiswi Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Kanaya Aquilla; Muhammad Ridwan Basalamah; Aleria Irma Hatneny (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of this research is to analyze the effect of attractiveness, expertise and trust of celebrities on consumer buying interest in Scarlett Whitening products. This study uses an explanatory research type using a quantitative approach. The sampling technique and the population used a non-probability sampling technique with a purposive sampling approach. Sources of data used in this study is primary data. Respondents in this study were students of the Islamic University of Malang Management Study Program Class of 2018-2019. The number of respondents 86 people. The analysis technique used in this research is multiple linear regression. Based on the results of research analysis, the variables of attractiveness, expertise, and trust have a simultaneous effect on consumer buying interest. There is a partial influence of the attractiveness, expertise, and trust variables on buying interest. Keywords: Attractiveness, Expertise, Trust,Purchase intention